The effect of the discovery learning model on students' mathematical reflective thinking skills - Fadhel Ahmad Meizano; Nurhanurawati; Mella Triana (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Mathematical reflective thinking is an essential higher-order thinking skill that supports students in analyzing, evaluating, and drawing conclusions during problem solving. This study aims to examine the effect of the Discovery Learning (DL) model on students' mathematical reflective thinking skills. The research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The population consisted of all Grade VIII students of SMP Negeri 9 Bandar Lampung in the 2024/2025 academic year, with two classes selected as the experimental and control groups through cluster random sampling. Data were collected using a mathematical reflective thinking skills test and analyzed using N-Gain analysis and an independent sample t-test. The results show that students taught using the DL model achieved higher posttest scores and greater improvement in mathematical reflective thinking skills compared to students taught through conventional learning. The average N-Gain of the experimental class was higher than that of the control class, and hypothesis testing indicated a significant difference between the two groups. These findings indicate that the Discovery Learning model has a positive and significant effect on students' mathematical reflective thinking skills and can be effectively implemented in mathematics learning.